OPTIMALISASI POTENSI LOKAL DAN KEARIFAN BUDAYA DALAM MEWUJUDKAN KEMANDIRIAN DAN KEBERLANJUTAN PEMBANGUNAN DI DESA SOKONG KECAMATAN TANJUNG KABUPATEN LOMBOK UTARA - Isnawati, Isnawati; Nurjannah, Alifah Siti; Agustin, Baiq Wilmalia; Riadah, Siti; Alfisahari, Andrea; Andriansyah, Diky; Deviani, I Gusti Ayu Shirin Kartika; Hamdayani, Septya; Yani, Indri Rachma; Rustan, Rustan; Simanjuntak, Rahel Tiona Gracella (Jurnal Wicara, 2025)
Sokong Village, Tanjung District, North Lombok Regency, boasts local potential, including natural resources in the livestock sector, trigona honey cultivation, and a wealth of cultural wisdom, which serve as key assets for village development. The University of Mataram's 2025 Community Service Program for Village Empowerment (KKN-PMD) implemented a series of community empowerment activities using an educational and participatory approach. Core activities included training in fermented feed and healthy livestock care to increase livestock productivity, training in trigona honey bee cultivation integrating care techniques and digital marketing, and the development of a culture-based tourism village through local wisdom mapping, cultural performances, and digital promotion training. Additionally, additional programs such as fun classes for children, nutrition education at integrated health posts (Posyandu), village administration assistance, and Independence Day celebrations have had a positive multidimensional impact. Program results demonstrated improved technical skills, the formation of independent trigona honey business groups, and an increased village appeal as a cultural tourism destination. This program has successfully promoted community economic independence and the preservation of cultural values ​​as a foundation for the sustainable development of Sokong Village.